03 Aspects of implicit learning and explicit learning of Spanish language - Viola ABITI GJYLI (Association of Social and Educational Innovation, 2015)
In teaching foreign languages, different theoretical concepts on presentation and language teaching methods have emerged from different traditions. In this work are examined theories of continuity between implicit and explicit learning, taking into account also how these theories are reviewed by many linguists. The benefits of explicit and implicit grammar knowledge in the process of learning a foreign language have increasingly been put at the center of language debates. The debate arises from the fact that speaking a language is an automatic action; therefore, it assumes an unconscious or implicit way of acquisition form, an act done instinctively. But teaching of grammar implies an act done consciously. In our case the main question is what the role between these two acquisition forms is. The central idea of this proposal was the development of the concept of grammar awareness - grammar consciousness raising.